Microstructure and grain refining performance of Ce on A380 alloy - Vončina M.; Mrvar P.; Petrič M.; Medved J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In the present work, the microstructure and grain refining performance of Ce on A380 alloy have been investigated, using thermal analysis, light microscopy with polarized light and scanning electron microscopy (SEM). The purpose was to study the influence of Ce addition on the formation of the microstructure. Ce changed the morphology of eutectic Al2Cu phase and caused small formation of primary crystals of αAl. Furthermore Ce phase was detected indicating quaternary phase AlCeCuSi (Al9Ce2Cu5Si3).